The resilience of income among urban poor communities in Kuala Lumpur - Sulaiman, Nor Fatimah Che; Muhamad, Suriyani; Zaidi, Mohd Azlan Shah; Aziz, Nazli; Nawawi, Mohd Nasir (Asian Development Policy Review, 2023)
The urban poor in Kuala Lumpur, especially those in the informal settlements, are increasingly at risk of decreasing standards of living, health, and livelihood. One of the strategies to overcome poverty is to build resilience for the poor, in line with the Sustainable Development Goals (SDGs) target to alleviate poverty through the resilience model. Therefore, the objective of this study is to develop a resilience model of income among urban poor communities in Kuala Lumpur. This study collected 481 respondents through the distribution of questionnaires. The data were analyzed using Descriptive Analysis and index development by Statistical Package for Social Science (SPSS). The findings of the study showed that a total of 383 respondents, or 96% of respondents, have incomes below RM4,000. The study also found that 33.5% of the total respondents are employed by government and private companies. The income resilience index showed that almost 90% of urban poor communities are at a moderate level, and 9% are at a low level. This indicates that the resilience of income in urban poor communities is still suppressed. This study is among a few that have been conducted to investigate the resilience of income among urban poor communities, particularly the People’s Housing Project (PPR) in Kuala Lumpur, Malaysia. To overcome poverty and promote resilience among these urban poor communities, the government should come out with relevant policies and strategies for upgrading the urban poor’s income to build resilience among urban poor communities in Kuala Lumpur.